Effect of Glutamine-Supplemented Extender on Kinematics and Quality of Cryopreserved Epididymal Sperm of Barb Stallions - Aouane, Nedjma; Metref, Ahmed Khireddine; Nabi, Ibrahim; Belala, Redha (The Indian Journal of Animal Reproduction, 2024)
The aim of the present study was to evaluate the effect of glutamine on the motility parameters after thawing of  epididymal semen of Barb stallions. Semen samples were collected from 22 testicles of slaughtered Barb stallions by  retrograde flushing technique. Semen samples were aliquoted and diluted with the following extenders, (1) base medium  (BM) (INRA96®+2.5%glycerol+2% egg yolk); (2) BM+25mM Glutamine (C25); (3) BM+50mM Glutamine (C50); (4)  BM+75mM Glutamine (C75) and (5) BM+100mM Glutamine (C100). The assessment of Kinematic parameters was  established after thawing by using SPA® spain CASA (Computer Automated Sperm Analyzer); and the plasma membrane  functional integrity was analyzed by HOST test. At low concentrations, the presence of glutamine (C25 and C50) improved  significantly (p
Keywords: Glutamine; Epididymal sperm; Cryopreservation; Barb stallions; CASA